THE ROLE OF PEDAGOGICAL SKILLS, TECHNIQUES, AND METHODS IN WORKING WITH CHILDREN (Neo Scientific Peer Reviewed Journal, 2025)
This article discusses the importance of pedagogical skills, techniques, andmethodologies in working with children to ensure that lessons are effective and understandable. Additionally, you will learn about modern psychological approaches, interesting methods, and their impact.